Ikhtiar Guru Agama dalam Membina Kesehatan Mental Generasi Muda di SMA Irsyadul Mubtadiin Gading Probolinggo - Qosim, Nanang (LP3M Universitas Islam Zainul Hasan Genggong, 2019)
Educational institutions are faced with the rapid development of millennial times, so that the impact of the progress of the era has positive and negative impacts, the negative impact issues that concern the public include actions and deviant behavior from the community, such as immorality, gambling, robbery, consuming drugs, drinks hard and so on.The deviant behavior is expected not to poison the young generation as the successor of the nation's life. The youth is the relay holder of the nation's future leadership, therefore the Irsyadul Mubtadiin High School educational institution strives as much as possible to educate and nurture the mental health of the young generation. Youth is a generation that is capable of achieving the nation's ideals to be proud of by all levels of society. Religious education taught by professional religious teachers is sought to be able to fortify the souls of the younger generation so that they are not affected by the current and negative effects of the changes and progress of the times. Keyword: Religion Teacher, Mental Health, Young Generation